The structure and meaning in Tshivenda traditional songs - Nemapate, Mmbulaheni Alfred (University of the North, 1999)
Refer to document
Theis (M.A. ) --University of the North, 1999
Keywords: Structure and meaning; Traditional songs; Venda tradition; Songs, Venda; Folk songs, Venda